Towards the reliable chemical stability testing of the single base gunpowder using a microcalorimetry method - Djokić Milan М.; Bajić, Zoran J.; Ignjatović, Vladimir D. (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: Gunpowder is a type of explosive material (EM), a mixture of chemical compounds capable of releasing their potential energy in a very fast exothermic chemical reaction. This paper investigates the single base gunpowder samples. Methods: Microcalorimetry (MC), or heat flow calorimetry (HFC), is the only modern method that monitors the direct cause of autoignition - the rate of heat release, which is a key factor for gunpowder storage explosive safety. It is based on high-sensitivity calorimeters which allow monitoring of chemical reactions at low speeds. The microcalorimeter "TAM III" was used and the method given by the NATO standard STANAG 4582. A very reliable result was obtained on the chemical stability of the observed single base gunpowder samples, as well as an assessment of its behavior in the next 10 years. Results: The thermal activity of gunpowder depends on several factors, the most important of which are: chemical composition, size and shape of the gunpowder grain, the degree of decomposition of the gunpowder, storage conditions, etc. Namely, it is a much more exact and consistent indicator of the chemical stability of gunpowder compared to the critical diameter. Conclusion: The MC method should be used both for monitoring the chemical stability of gunpowder during storage and for the prediction of the service life of gunpowder.